A qualitative study of stress and coping when transitioning to adulthood with autism spectrum disorder. Issue 3 (26th May 2016) - First, Jennifer; Cheak-Zamora, Nancy C.; Teti, Michelle
ABSTRACT: The transition into adulthood can be stressful and challenging for adolescents with autism spectrum disorder (ASD) and their caregivers. Few studies have examined the perspectives of adolescents with ASD and their caregivers during the transition to adulthood. This qualitative study utilized the method of four focus groups with 19 caregivers and 13 adolescents with ASD. Main themes of stress reported by participants included encountering challenges in accessing services, difficulties with adapting to transition changes and managing multiple responsibilities, and vocation and higher education challenges. Main themes of coping reported by participants included accessing support from community services, receiving support from family, friends, and teachers, and seeking opportunities for self-determination. These findings provide insight into adolescent and caregiver perceptions of the challenges they face when youth transition to adulthood with ASD, along with resources and coping strategies they have found helpful. Implications are provided to assist social workers and practitioners in supporting adolescents with ASD and their caregivers during the transition to adulthood.